The expression of the epidermal growth factor (EGF) during odontogenesis: - Breno C. Peixoto; Cássio R. R. dos Santos; Conceição E. Canuto (Brazilian Dental Science)
The objective of this study was to verify, through the technique of Immunohistochemistry, the expression of the epidermal growth factor (EGF) in the odontogenesis of the first upper molar in Mus musculus mice, relating it to the microscopic morphologic analysis. The sample consisted of 23 animals, with age from the 13th day of intrauterine life to the 20th day of postnatal life. The results showed EGF being expressed by several tissues and cells participating of the odontogenesis. However the dental follicle was the only place where the expression of EGF was constant for the whole process, characterizing it as one of the regulating tissues of odontogenesis.